Studi Komparasi Strategi Word Square DenganEveryone Is A Teacher Here Terhadap Hasil Belajar IPS Kelas III MIM Srebegan Tahun Pelajaran 2015/2016 - Diah Ratnasari, Novita; , Drs. Mulyadi SK, M.Pd (2016)
The objectives of the research are: (1) to describe differences of the learning outcome in using Word Square strategy and Everyone Is A Teacher Here strategy in "IPS" learning at the third grade of MIM Srebegan in the academic year of 2015/2016 (2) to describe what strategy that has greater influence toward learning outcome of social science learning at the third grade of MIM Srebegan in the academic year of 2015/2016. The subject of the research was the students at the third grade of MIM Srebegan in the academic year of 2015/2016. The research is a quantitative research. The technique of the data analysis by using uji-t that the previous of analysis prerequisite test, are homogeneity and normality test. Based on data analysis with the significant degree 5% it again tcount>ttabel is 9,004>1,998. Based on the percentage of average I> the percentage average II, 83,79310345 > 79,4444, can be conclude that (1) can be found of social science learning at the third grade of MIM Srebegan in the academic year of 2015/2016 (2) Everyone Is A Teacher Here have a large of influence compare with learning word square strategy in the result of increasing social science learning at the third grade of MIM Srebegan in the academic year of 2015/2016. Keyword: learning result, Word Square Strategy, Everyone Is A Teacher Here Strategy